The Hand and the Glove - Machado de Assis, 1839-1908 (Book collections on Project MUSE., 2015)
The later novels of Machado de Assis -- notably Dom Casmurro and Esau and Jacob -- are well known in this country, but the earlier novels have never been translated. Here, in The Hand and the Glove (the Brazilian master's second novel), rendered in English for the first time by Albert I. Bagby, Jr., readers will find a younger, gentler Assis, writing a romantic comedy that is yet permeated with the lively wit characteristic of his later works. The story is a simple one-of love lost and love found. Of love lost by Estêvão, amiable but vacillating, who is bemused by his own romantic posturing,